2006
DOI: 10.1593/neo.06409
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of PIAS3 Suppresses Cell Growth, Restores the Drug Sensitivity of Human Lung Cancer Cells in Association with PI3-K/Akt Inactivation

Abstract: Constitutively activated signal transducers and activators of transcription (STAT) are reported to cause uncontrolled transmission of growth signals. In this study, we analyzed the roles of an inhibitor of STAT, protein inhibitor of activated STAT (PIAS) 3, in the development of lung cancer. Treatment with an inhibitor of phosphatidylinositol 3-kinase, LY294002, retarded the growth of human lung cancer cells and rendered them more sensitive to chemotherapeutic agents. However, the inhibition of JAK/STAT by AG4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
53
0
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(55 citation statements)
references
References 35 publications
1
53
0
1
Order By: Relevance
“…2), the downregulation of the PIAS3 protein might involve factors regulating its stability. Phosphoinositide 3-kinase/AKT has been linked to PIAS3 activity (16) and nitric oxide has been found to destabilize PIAS3 and regulate its sumoylation (35). A cross-talk between hSiah2 (seven in absentia) and PIAS3 modulates PIAS-dependent activation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…2), the downregulation of the PIAS3 protein might involve factors regulating its stability. Phosphoinositide 3-kinase/AKT has been linked to PIAS3 activity (16) and nitric oxide has been found to destabilize PIAS3 and regulate its sumoylation (35). A cross-talk between hSiah2 (seven in absentia) and PIAS3 modulates PIAS-dependent activation.…”
Section: Discussionmentioning
confidence: 99%
“…A few studies have addressed the effects of exogenous PIAS3 overexpression in cancer cells: (a) about 89% of glioblastoma samples were found to be PIAS3 negative and P-STAT3 positive and the ectopic expression of PIAS3 in a glioblastoma cell line caused the inhibition of the transcriptional activity of STAT3 (14); (b) overexpression of PIAS3 in melanoma and lung cancer cell lines inhibited cell growth and suppressed STAT3 activity (15,16); (c) overexpression of PIAS3 in v-Src-overexpressing tumor cells suppressed STAT3 target gene expression (17); (d) exogenous expression, mediated by infection with an adenovirus encoding kChaP/PIAS3β in prostate cancer cells, induced apoptosis and reduced growth of prostate tumor xenografts in nude mice (18). These studies indicate that PIAS3 can counteract the function of constitutively active STAT3.…”
Section: Introductionmentioning
confidence: 99%
“…In vitro, PIAS3 down-regulated the nuclear factor-nB pathway by interacting with p65 and repressing its transcriptional activity (91). PIAS3 also modulated the phosphoinositide-3 kinase pathway by interacting with AKT and suppressing its phosphorylation and activation (92). Studies in various cell lines showed that PIAS3 overexpression affected AKT signaling in both prostate and lung cancer cells, with subsequent effects on cell growth and apoptosis (92,93).…”
Section: Endogenous Negative Regulation By Pias3mentioning
confidence: 99%
“…PIAS3 also modulated the phosphoinositide-3 kinase pathway by interacting with AKT and suppressing its phosphorylation and activation (92). Studies in various cell lines showed that PIAS3 overexpression affected AKT signaling in both prostate and lung cancer cells, with subsequent effects on cell growth and apoptosis (92,93). PIAS proteins also regulated the transcriptional activity of SMAD proteins, the downstream targets of transforming growth factor-h signaling (25).…”
Section: Endogenous Negative Regulation By Pias3mentioning
confidence: 99%
“…Further, PIAS3 overexpression in breast cancer cell lines was shown to significantly modulate STAT5-mediated gene expression and induce cellular apoptosis [40]. Finally, overexpression of PIAS3 suppresses cell growth and restores the drug sensitivity of human lung cancer cells [41]. To date, only cell line work supports the evidence for PIAS downregulation of the STAT pathway but no clear evidence exists for hypermethylation of the PIAS promoter in human solid tumors.…”
Section: Hypermethylation Of Stat Inhibitors In Solid Tumorsmentioning
confidence: 99%